On the colonial origins of agricultural development in India : a re-examination of Banerjee and Iyer, ‘History, institutions and economic performance’ /: a re-examination of Banerjee and Iyer, ‘History, institutions and economic performance’. (June 2012) - Iversen, Vegard; Palmer-Jones, Richard, 1946-; Sen, Kunal, 1961-
No abstract available